Robust Variable Structure Control Approach of Two Series-Connected Five-Phase PMSMs Under Healthy and Faulty Operation Modes - Ali Ajmi (17983771) (2023)
In this paper a robust vector control method based on second order Super Twisting Sliding Mode Controllers (STSMCs) for two series-connected Five-Phase Permanent Magnet Synchronous Motors (FP-PMSMs) supplied by a single five-leg inverter is suggested. The vector control method of the two series-connected FP-PMSMs is based on six regulation loops for currents and speeds that are usually based on proportional integral controllers. Thus, the first aim of this paper is to replace the proportional integral controllers by the proposed second order STSMCs in order to enhance the control system performance in terms of robustness under uncertainties, external disturbances and tracking accuracy. Indeed, the second order STSMCs are proposed in order to overcome the limitations of the proportional integral controllers in terms of sensitivity against the variations in FP-PMSMs parameters and load disturbances and to overcome the first order sliding mode control chattering problem. However, the suggested second order STSMCs require information about the load torques applied to the two FP-PMSMs, which are estimated using sliding mode load torque observers hence reducing the cost and maintenance rate of the electromechanical system due to the elimination of load sensors. Our simulation studies conducted in MATLAB/Simulink check whether the proposed topology of the two series-connected FP-PMSMs controlled by the suggested vector control based on second order STSMCs can regulate the speed at the same time under various conditions. These conditions include load disturbances, parameter variations in both machines, and disturbances resulting from the opening of a phase. Our objective is to demonstrate the excellent robustness of the suggested second order STSMCs based vector control approach in terms of independent speed control of the two FP-PMSMs even at low or reversed speeds, compared with the conventional proportional integral control strategy. In this comparative study, various performance indices are used to demonstrate the robustness of the proposed vector control method based on second order STSMCs control strategy in comparison to the vector control method based on proportional integral controllers. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3311029